Establishment of reference intervals for complete blood count in healthy adults at different altitudes on the Western Sichuan Plateau - QiaoLing Wang; JiaYu Liu; ShengLin Hu; JunWu Du; ShuZhi Zhou; ZhengLin Huang; Yanwu Liu; Kongjie Yang; Ling Zhang; Jian Yang; Qing Yuan (Frontiers in Medicine)
BackgroundA detailed reference range for complete blood count of healthy adults in the Western Sichuan Plateau region is unavailable. This study aimed to explore changes in complete blood count (CBC) in healthy adults across high-altitude regions of Ganzi Prefecture, Sichuan Province, to establish altitude-specific reference intervals and improve diagnostic accuracy and provide tailored clinical guidance for residents in these areas.MethodsCBC data from 3,485 healthy individuals from four altitudes—Guza (1,400 m), Lucheng (2,500 m), Luhuo (3,200 m), and Litang (4,100 m)—were collected between January 2022 and December 2023. The data were analyzed by sex, altitude, age groups, and their interactions to establish reference intervals.ResultsCBC indicators showed significant changes with increasing altitude. Red blood cell (RBC) count, hemoglobin (HGB), hematocrit (HCT), white blood cell (WBC) count, and platelet (PLT) count all significantly increased as altitude rose (p < 0.05). Males had significantly higher RBC, WBC, and PLT counts than females across all altitudes (p < 0.05), except in Litang, where HCT and HGB differences between sexes were not significant (p < 0.05). With increasing age, RBC count, HCT, HGB, WBC count, and PLT count increased in both sexes. Most CBC indicators in the study population exceeded national reference intervals, except for HGB and HCT in males from Guza and Lucheng.ConclusionThis study established CBC reference intervals for the high-altitude regions of Ganzi Prefecture, revealing significant variations by altitude, sex, and age. These findings provide valuable insights for improving disease diagnosis and medical care for high-altitude residents.